Isolation of bacteria in effective microorganisms (EM) suitable for degradation of thiosulfate - Zakaria, Zainoha; Md. Salleh, Madihah; Ashaari, Nur Suhanawati; Aziz, Madzlan (Faculty of Science, 2009)
A total of 60 potential sulfur-oxidizing bacteria isolated from the Effective Microorganisms (EM) sample were screened for sulfide oxidase producer. Out of 60 isolates, 11 strains were able to produce sulfide oxidase and the most superior sulfide oxidase producer was known as strain SO02. Strain SO02 produced 6.83 U/ml sulfide oxidase with specific activity of 2.32 U/mg. Strain SO02 was later identified as Serratia sp. via biochemical test and 16S rRNA gene sequence analysis. The optimum condition of sulfide oxidase production was obtained at pH 5.0, 30ËšC in the presence 0.2% (w/v) peptone and 0.5 mM thiosulfate. Under optimized condition, sulfide oxidase activity was 3.848 U/ml with specific activity of 5.460 U/mg. There were 60.2% and 90.7% improvements in sulfide oxidase production and specific activity after the optimization studies, respectively. Development of oxygen control strategy towards sulfide oxidase production showed that the most favorable condition for the production of sulfide oxidase was without dissolved oxygen control strategy. Sulfide oxidase activity and the specific activity without oxygen control strategy were obtained up to 4.843 U/ml and 6.764 U/mg, respectively. However, sulfide oxidase production under oxygen control condition was 13% lower as compared to the condition without oxygen control with sulfide oxidase activity of 4.216 U/ml. This might occurred due to low oxygen concentration in the fermenter where oxygen was required in the sulfur oxidation. The specific oxygen uptake rate using strategy of without dissolved oxygen control was 0.499 mg O2/ g cell/ min.